The Ecological Wisdom of Banyumas Folklor as Literacy Material for Children - Septi Yulisetiani; Detria Nur Aini Sutrisno (Javanologi: International Journal of Javanese Studies, 2023)
This study aims to describe the ecological wisdom contained in Banyumas folklore. The aim is to find out the forms of ecological wisdom of the Javanese people. The data source for this research is Banyumas folklore in the form of stories. Some of these stories include: Asal Mula Sungai Serayu; Kerajaan Dayeuhluhur Cikal Bakal Kabupaten Cilacap; Sepatnunggal; Lengger Dempet; Asal Usul Dusun Sitinggil. The research method used is qualitative with a literary ecological approach. Data were collected by means of literature study and interview techniques. Data analysis techniques were performed using interactive analysis techniques. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of the study show that the various forms of ecological wisdom of the Javanese people in Banyumas folklore. The ecological wisdom of the Javanese people in the story includes wisdom in managing natural resources and wisdom in preserving nature. Natural resources are one of the sources of human life. Natural resources are considered as something important in life. For this reason, humans are given teachings to protect natural resources. Utilization of natural resources must be carried out in a balanced way with activities to preserve nature. Efforts to manage and preserve natural resources are hereditary teachings that are conveyed in the story.Keywords: Kearifan ekologis; Folklor; Jawa; Banyumas